2016
DOI: 10.1111/his.13092
|View full text |Cite
|
Sign up to set email alerts
|

Challenging diagnostic issues in adenomatous polyps with epithelial misplacement in bowel cancer screening: 5 years’ experience of the Bowel Cancer Screening Programme Expert Board

Abstract: The diagnostic difficulties of differentiating epithelial misplacement from invasive cancer in colorectal adenomatous polyps have been recognised for many years. Nevertheless, the introduction of population screening in the UK has provided extraordinary diagnostic problems. Larger sigmoid colonic adenomatous polyps, those most likely to show epithelial misplacement, are specifically selected into such screening programmes because these polyps are likely to bleed and screening is based on the detection of occul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 21 publications
5
33
0
Order By: Relevance
“…45 It is very difficult to account for this because diagnosis of T1 CRC in pedunculated lesions is a contemporary challenge, even for expert pathologists, and a golden standard does not exist. 45,46 The incidence of 5.2% used for our analysis seems justified because there were also cases revised as T2 CRC, and this is in good agreement with previous reported incidence rates varying between 3% and 7%. [4][5][6][7] Ikematsu et al 2 showed recurrence rate to be significantly higher in patients with high-risk T1 rectal cancer treated with endoscopic resection without adjuvant surgery (16.2%) compared to similarly treated high-risk T1 colon cancer (1.4%).…”
Section: Discussionsupporting
confidence: 89%
“…45 It is very difficult to account for this because diagnosis of T1 CRC in pedunculated lesions is a contemporary challenge, even for expert pathologists, and a golden standard does not exist. 45,46 The incidence of 5.2% used for our analysis seems justified because there were also cases revised as T2 CRC, and this is in good agreement with previous reported incidence rates varying between 3% and 7%. [4][5][6][7] Ikematsu et al 2 showed recurrence rate to be significantly higher in patients with high-risk T1 rectal cancer treated with endoscopic resection without adjuvant surgery (16.2%) compared to similarly treated high-risk T1 colon cancer (1.4%).…”
Section: Discussionsupporting
confidence: 89%
“…There are a significant number of difficult cases that can be misinterpreted by the unwary, and displacement of adenomatous epithelium into the submucosa (pseudoinvasion) is particularly problematic. In a review of difficult cases in the NHS BCSP, 69% of lesions originally reported as malignant were downgraded to benign on expert review . For this reason, the NHS BCSP Pathology Committee have recommended that all cancers diagnosed in the programme should be reported by two independent pathologists, to reduce the risk of overtreatment .…”
Section: Introductionmentioning
confidence: 99%
“…It can be the result of a torsion or intraluminal trauma of large pedunculated polyps of the distal colon, or it may be a consequence of a previous biopsy. Adenomas with epithelial misplacement (pseudoinvasion) can be difficult to distinguish from adenomas with early adenocarcinoma [ 5 7 ]. The correct diagnosis is crucial for the choice of optimal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The correct diagnosis is crucial for the choice of optimal treatment. For adenoma and adenoma with epithelial misplacement, endoscopic removal is sufficient, whereas malignant adenomas (early carcinomas) may require surgical treatment, since they are capable of metastasizing [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation